Collapsing cylindrically symmetric filamentary stellar object - Saleem, Sana; Ibrar, Andleeb; Almusawa, Musawa Yahya; Eldin, Sayed M.; Asjad, Muhammad Imran (Frontiers in Astronomy and Space Sciences, 2023)
This work investigates the collapsing behavior of filamentary objects under the influence of Dark Matter. For this purpose, we use $f(R,T)$ gravity as a candidate for dark matter. The collapse equation is obtained by imposing the Darmois junction condition at the collapsing boundary. At the collapsing boundary, it is observed that the radial pressure is non-zero and is proportional to the field time-dependent component. Finally, we check the relationship between gravitational waves and dark source terms. It is concluded that the dark source terms disturbs the propagation of gravitational waves.